DOEGE-POTTER SYNDROME ARISING FROM AGGRESSIVE RECURRENT FIBROUS TUMOUR OF THE LUNG: A CASE REPORT - Azmi, Nurain; Ali, Masliza Hanuni Mohd; Azman, Siti Sanaa Wan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Doege-Potter Syndrome (DPS) is a rare paraneoplastic syn- drome characterized by hypoinsulinemic hypoglycaemia. It typically arises in patients with mesenchymal tumours, particularly fibrous tumours of the lung. DPS is secondary to ectopic secretion of high-molecular-weight insulin-like growth factor (IGF)-2 that induces hypoglycemia. CASE We report a 56-year-old male with an underlying solitary fibrous lung tumour that was resected in 2013, which recurred in 2023 and was deemed unresectable. He was to undergo chemotherapy. However, while waiting, he presented neuroglycopenia with a capillary blood glucose of 1.9 mmol/L, reversed with glucose administration. Imaging studies revealed a large pleural-based lesion on the left with an interval increment in size, with its largest diameter at 20.6 cm and worsening mass effect. Histopathology report from CT-guided biopsy confirmed diagnosis of recurrent fibrous tumour with no malignant features. Renal and liver profiles were normal, and HbA1c was 4.3%. Paired random blood glucose was 2.8 mmol/L, with suppressed C-peptide and insulin levels of 31.81 pmol/L (NR 366.66-1466.65) and <1.39 pmol/L (NR 17.8- 173), respectively. Serum IGF-1 was normal at 166.2 ng/ml (NR 54.3-194.2). Serum IGF-2 was 479 ng/ml (NR 333-967), with an IGF-2:IGF-1 ratio of 3, supporting the diagnosis of IGF-2-mediated hypoglycemia. We started him with oral prednisolone 0.5 mg/kg/day, and the hypoglycaemia improved. Unfortunately, he succumbed to respiratory failure due to advanced tumour progression. Given the clinical findings and available biochemical markers, this case is consistent with a diagnosis of non-islet cell tumour hypoglycaemia (NICTH). CONCLUSION This case emphasizes the association between solitary fibrous tumours of the lung and DPS, highlighting the potential for recurrence of the tumour and persistent paraneoplastic effects. Early recognition and appropriate management of DPS are crucial in improving patient outcomes, such as the commencement of corticosteroids, while awaiting definitive treatment.